Exosome-Based Cancer Therapy: Implication for Targeting Cancer Stem Cells - Wang, Jinheng; Zheng, Yongjiang; Zhao, Meng (Frontiers in Pharmacology, 2017)
Drug resistance, difficulty in specific targeting and self-renewal properties of cancer stem cells (CSCs) all contribute to cancer treatment failure and relapse. CSCs have been suggested as both the seeds of the primary cancer, and the roots of chemo- and radio-therapy resistance. The ability to precisely deliver drugs to target CSCs is an urgent need for cancer therapy, with nanotechnology-based drug delivery system being one of the most promising tools to achieve this in the clinic. Exosomes are cell-derived natural nanometric vesicles that are widely distributed in body fluids and involved in multiple disease processes, including tumorigenesis. Exosome-based nanometric vehicles have a number of advantages: they are non-toxic, non-immunogenic, and can be engineered to have robust delivery capacity and targeting specificity. This enables exosomes as a powerful nanocarrier to deliver anti-cancer drugs and genes for CSC targeting therapy. Here, we will introduce the current explorations of exosome-based delivery system in cancer therapy, with particular focus on several exosomal engineering approaches that have improved their efficiency and specificity for CSC targeting.